Clinicoepidemiological profile of pediatric psoriasis: Experience from a tertiary care center - Vibhu Mendiratta; Amit Kumar Meena; Ashna Jain; Bharati Verma (Wolters Kluwer Medknow Publications, 2023)
Introduction: Psoriasis is a common skin disorder and is relatively less studied in children. The objective of this study was to evaluate the clinical and epidemiological profile of pediatric psoriasis (PP). Materials and Methods: All patients of psoriasis (age <18 years) who visited PP clinic from January 2017 to September 2021 were included in this record-based study, which was conducted in a tertiary care center in North India. Results: Records of 100 patients were analyzed, with female-to-male ratio of 1:1. The mean age of diagnosis was 10.87 ± 3.96 years. The most common initial site of onset was elbows, followed by knees and soles. The most common subtype was plaque psoriasis followed by palmoplantar and guttate types. Average body surface area (BSA) involved was 5.43% with majority (49%) had involvement of 3%-10% BSA. Average psoriasis area and severity index (PASI) in our study was 2.47. PASI >10 was seen in only 5% of patients. Joint involvement was found in 7% of patients and nail changes in 54%. Infection (15%) was the most common aggravating factor, followed by trauma and stress. Koebner phenomenon was present in 15% of patients. Family history of psoriasis was reported in 22% of the patients. A history of other autoimmune disease was present in 5 patients, out of which vitiligo and hypothyroidism was present in 2 patients each and 1 had morphea. Conclusion: PP is a persistent, chronic condition that can have significant psychosocial and emotional implications. For better understanding of PP, more population-based studies are required from different parts of the world.